European Public Prosecutor – Need for Establishment and Role in the Legal System of The European Union - Bijeljanin, Petko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
In this paper, the author speaks about the key aspects of the European Public Prosecutor’s Office. The Lisbon Treaty provides a legal basis for the Member States of the European Union (EU) to establish a European Public Prosecutor (EPP) with competence to prosecute, in the courts of the Member States, crimes against the financial interests of the Union. It has to be underlined that the EU has a strong interest in counteracting financial crimes and fraud against the EU budget, as those crimes hamper the trust in the market and undermine consumer confidence to engage in internal market transactions. The creation of the EPPO marks a fundamental development in the fight against crimes affecting the EU’s budget. It is also an important step towards creating a common criminal justice area in the European Union as a whole. Processes of globalization have multiplied cross-border links and intensified interconnectedness in the economic, political and cultural spheres. Inevitably, criminal enterprises have also become global making many harmful consequences for the EU budget. It is necessary to take into account the modern technology that facilitates the spreading of cross-border crime and its sophisticated forms that require cooperation in criminal matters.